2021
DOI: 10.1044/2021_persp-21-00037
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Face Masks, and Social Interaction: How a Global Pandemic Is Shining a Light on the Importance of Face-to-Face Communication

Abstract: Purpose The purpose of this article is to discuss the impact of COVID-19 mitigation strategies on face-to-face communication. The article covers three main areas: the effect of face masks and social distancing on aspects of communication, including speech production, speech recognition, and emotion recognition; the effect of face masks on access to visual speech cues; and downstream effects of poor speech recognition on language and cognitive abilities. Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The potential barriers to language imposed by face-mask use may be amplified by the context in which language is occurring. For example, noisy language environments such as those that occur in preschool classrooms may compound difficulties accessing language occurring through a mask ( Crandell and Smaldino, 2000 ; Klatte et al, 2013 ; Grieco-Calub, 2021 ). Further, face-mask use may differentially affect children with hearing loss who often experience inconsistent or distorted access to acoustical information compared to their peers with typical hearing.…”
Section: Introductionmentioning
confidence: 99%
“…The potential barriers to language imposed by face-mask use may be amplified by the context in which language is occurring. For example, noisy language environments such as those that occur in preschool classrooms may compound difficulties accessing language occurring through a mask ( Crandell and Smaldino, 2000 ; Klatte et al, 2013 ; Grieco-Calub, 2021 ). Further, face-mask use may differentially affect children with hearing loss who often experience inconsistent or distorted access to acoustical information compared to their peers with typical hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Patients and clinicians struggled to hear each other, and a level of connection could be lost. Previous research has identified that mask-wearing can inhibit communication between clinicians and patients( 45 , 46 ) affect emotion recognition and inhibit impressions of trustworthiness( 47 , 48 ), and cause moral distress to staff( 49 ). In this study, participants reported difficulty demonstrating empathy to patients when PPE concealed their facial expressions and non-verbal cues, at a time when compassion and responsiveness were most needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, face masks filter the acoustic speech signal, which can further reduce speech recognition. Certain types of masks may reduce the signal more than others (Grieco-Calub, 2021 ). It has been recommended that face shields or face masks with transparent windows should be used to provide visual cues and facilitate speech recognition (Thibodeau, Thibodeau-Nielsen, Tran, & De Souza Jacob, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, face masks cover visual cues and expressions (such as smiles, frowns and smirks) which are crucial when targeting pre-linguistic skills in ECI (Atcherson et al, 2017;Keen et al, 2016). In addition, social distancing may cause speech to be less audible or even completely unheard (Grieco-Calub, 2021).…”
Section: Challengesmentioning
confidence: 99%